Effect of Reinforcement Volume Ratio on Thermal Conductivity of SiO2 Reinforced Al Matrix Composite Produced by Vacuum Infiltration Method - CALIN, RECEP (Asian Journal of Chemistry, 2009)
In this study, SiO2 powders with 105 μm particle size were filled in quartz tubes freely to form 30, 40, 50 % reinforcement volume ratios. Liquid Al7075 alloy was vacuum infiltrated into the SiO2 compact under the same vacuum condition, the same time and at the same temperature in normal atmosphere for 3 min. After vacuuming, infiltration height and density of product composite have been determined. Microstructures of composites were investigated by SEM analysis. Two methods, finite element analysis method and experimental method, were used to determine thermal conductivity. The results of these methods were evaluated and compared. It has been found that the values of two different methods were quite near each other and thermal conductivity of composite increased with decreasing reinforcement volume ratio.